Effects of selected treatments on properties of pineapple leaf fibre reinforced high impact polystyrene composites - Siregar, Januar Parlaungan (2011)
The objective of this study was to investigate the physical, mechanical, and thermal properties of pineapple leaf fibre (PALF) reinforced high impact polystyrene (HIPS) composites. PALF is one of the natural fibres that is rich in cellulose and has high tensile strength properties. The fibres were obtained from the leaves of the pineapple plant. The PALF fibres were ground and sieved into different sizes of fibres; 10-40, 40-60 and 60-80 meshes. Six different fibre loadings of 0%, 10%, 20%, 30%, 40% and 50% by weight of pineapple fibre were used to reinforcement in high impact polystyrene. Mixing PALF fibre and HIPS was carried out using a melt mixer and then the resulting material was compressed in the mould using a Carver laboratory press at temperature 165°C. The results showed that the addition of untreated PALF fibre to reinforce HIPS has decreased the tensile strength, flexural strength, impact strength of composites but increased the tensile moduli, flexural moduli and hardness of the composites. The decrease of the strength of HIPS/PALF composites was due to the poor compatibility of hydrophilic PALF and hydrophobic HIPS matrix resulting in poor dispersion of fibre in the matrix and weak interfacial bonding between the fibres and HIPS matrix. Consequently this study also investigated the effect of alkali treatment and compatibilising agent to improve the mechanical and thermal properties of the composites. The PALF fibres were soaked in two different concentrations of NaOH solution which were fixed at 2% and 4% of sodium hydroxide (NaOH) solution. Two types of compatibilising agent were used in this research, namely polystyrene-block-poly(ethylene-ran-butylene)-block-poly(styrene-graft-maleic anhydride) and poly(styrene-co-maleic anhydride). The addition of fibre treatment and compatibilising agent has improved the mechanical and thermal properties of PALF/HIPS composites. The study of the effect electron beam irradiation and the addition of croslinking agent also increased the mechanical properties of the composites.